Expression, tissue localization and synergy of antimicrobial peptides and proteins in the immune response of the oyster Crassostrea gigas - Schmitt, Paulina; De Lorgeril, Julien; Gueguen, Yannick; Destoumieux-garzon, Delphine; Bachere, Evelyne (Developmental & Comparative Immunology, 2012)
Diverse families of antimicrobial peptides and proteins have been described in oysters. We investigated here how antimicrobials are involved in the immune response against a pathogenic strain of Vibrio splendidus. Oyster antimicrobials were shown to display a wide variety of expression profiles in hemocyte populations and tissues. Oyster defensins are constitutively expressed in specific tissues such as mantle (Cg-Defm) or hemocytes (Cg-Defhs), while Cg-BPI is inducible and Cg-Prp appears down-regulated in hemocytes upon infection. The migratory behavior of hemocytes that express the different antimicrobials was found to be involved in the oyster response to a pathogenic Vibrio infection. Indeed, it contributes to colocalize several antimicrobials that were shown here to have synergistic activities. We propose that such a synergy, which was evidenced both within and between families of antimicrobials, might compensate for the low concentration of antimicrobials in oyster tissues. (c) 2012 Elsevier Ltd. All rights reserved.